MRI-detected osteitis is not associated with the presence or level of ACPA alone, but with the combined presence of ACPA and RF. Issue 1 (December 2016) - Boeters, Debbie; Nieuwenhuis, Wouter; Verheul, Marije; Newsum, Elize; Reijnierse, Monique; Toes, René; Trouw, Leendert; van der Helm-van Mil, Annette
Abstract Background In rheumatoid arthritis (RA) bone marrow edema (BME, osteitis) and anti-citrullinated protein antibodies (ACPA) are associated with radiographic progression. ACPA have been associated with BME, but it is unknown if this association is confined to ACPA and BME. We performed cross-sectional analysis of the association of ACPA, rheumatoid factor (RF) and anti-carbamylated protein (anti-CarP) antibodies with BME and other types of inflammation (synovitis, tenosynovitis) detected by magnetic resonance imaging (MRI). Methods Disease-modifying antirheumatic drug (DMARD)-naïve patients with early arthritis (n = 589), included in the Leiden Early Arthritis Clinic cohort, underwent contrast-enhanced 1.5 T MRI of unilateral wrist, metacarpophalangeal and metatarsophalangeal-joints at baseline. BME, synovitis and tenosynovitis were scored by two readers. ACPA, rheumatoid factor (RF) and anti-CarP were determined at baseline. Results In univariable analyses ACPA-positive patients had higher BME scores than ACPA-negative patients (median 4.5 vs. 2.0, p  < 0.001), but not more synovitis and tenosynovitis. Also RF (median 3.75 vs. 2.0, p  < 0.001) and anti-CarP antibodies (median 3.5 vs. 2.5, p  = 0.012) were associated with higher BME scores. Because the autoantibodies were concomitantly present, analyses were stratified for the presence of different autoantibody combinations. ACPA-positive (ACPA+), RF-negative (RF-), anti-CarP-negative (anti-CarP-) patients did not have higher BME-scores than ACPA-negative (ACPA-), RF-, anti-CarP- patients. However ACPA+, RF-positive (RF+), anti-CarP- patients and ACPA+, RF+, anti-CarP-positive (anti-CarP+) patients had higher BME scores than ACPA-, RF-, anti-CarP- patients (median 5.0 and 4.5 vs. 2.0, p  < 0.001 andp  < 0.001). ACPA levels were not associated with BME scores. Analyses within RA- and UA-patients revealed similar results. Conclusions The presence of ACPA alone or ACPA level was not statistically significantly associated with BME scores, but the combined presence of ACPA and RF was associated with more BME. This suggests an additive role of RF to ACPA in mediating osteitis.